Response of Growing Dairy Bulls to Dietary Tannin in Rations with Varying Energy Levels - J. B. Poblete; A. A. Angeles; E. M. Agbisit, Jr.; M. V. O. Espaldon (Tropical Animal Science Journal, 2020)
This study was conducted to determine the effect of dietary tannin on growth performance, rumen fluid characteristics, and apparent total-tract digestibility in growing Holstein-Friesian x Sahiwal bulls fed low and high energy rations. Eighteen growing bulls with initial body weight (BW) of 162.8±12.7 kg at 15±0.80 months were used in an unbalanced randomized complete block design set-up in a 2x2 factorial arrangement. The experimental animals were blocked by their respective BW. Animals were fed with concentrates containing metabolizable energy (ME) at 2.47 and 2.72 Mcal/kg without or with 20g/kg tannin in dry matter basis. At the final week of the trial, rumen fluid and fecal samples were collected for the rumen fluid characteristics and apparent total-tract digestibility analyses. No differences (p>0.05) were observed between the growth performance, rumen gas production, volatile fatty acids as well as organic matter, crude protein, and energy digestibility. High energy concentrates had higher (p<0.05) dry matter and neutral detergent fiber digestibility than low energy concentrates. Low energy concentrates without tannin had cheaper (p<0.001) total feed cost but feed cost per kilogram BW gain was similar (p>0.05) across treatments. Feed savings costs of US$ 17.58 per animal were attained in feeding low energy concentrates without tannin. Therefore, feeding concentrates containing 2.47 Mcal/kg ME without additional tannin can still be fed economically to growing cattle without any adverse effect on growth, ruminal fermentation characteristics, and apparent total-tract digestibility.